Feasibility and safety of liver transplantation or resection after transarterial radioembolization with Yttrium-90 for unresectable hepatocellular carcinoma. Issue 11 (November 2019) - Labgaa, Ismail; Tabrizian, Parissa; Titano, Joseph; Kim, Edward; Thung, Swan N.; Florman, Sander; Schwartz, Myron; Melloul, Emmanuel
Abstract: Background: The benefit of transarterial radioembolization (TARE) in patients with unresectable hepatocellular carcinoma (HCC) is increasingly evidenced. However, data on outcome of liver transplantation or resection after TARE remain scarce. This study aimed to assess the safety and feasibility of surgery after TARE in patients with unresectable HCC. Methods: Patients exclusively undergoing TARE followed by either orthotopic liver transplantation (OLT) or liver resection (LR) for HCC between 2012 and 2016 were included. Primary outcomes were postoperative morbidity and mortality. Secondary outcomes were overall survival (OS) and response to TARE. Results: Among 349 patients with HCC treated with TARE, 32 (9%) underwent either OLT (n = 22) or LR (n = 10), which represent the study cohort. In this group, TARE induced decreased viable nodules (p < 0.001), an efficient downsizing (p < 0.001) as well as a significant downstaging based on BCLC classification (p < 0.001). Overall, major complications and mortality after surgery occurred in 5 (16%) and 1 (3%) patients, respectively. For the whole study cohort, OS was 47 months while survival rates at 1-, 3- and 5-years reached 97%, 86% and 86%, respectively. Discussion: Liver surgery after TARE is feasible and safe. This strategy allows to offer a curative treatment in a subset of patients with unresectable HCC.